2020
DOI: 10.1007/s11368-020-02644-w
|View full text |Cite
|
Sign up to set email alerts
|

Likely controls on dissolved reactive phosphorus concentrations in baseflow of an agricultural stream

Abstract: Purpose High baseflow phosphorus (P) concentrations increase the likelihood of periphyton blooms. Several physical and chemical factors can control baseflow P concentrations such as hydraulic exchange with groundwater, particle size-sorting, redox chemistry and different sediment sources. We hypothesized that of these sources, anoxic sediments would allow P-rich groundwater to influence baseflow P concentrations the most and that the measurement of the equilibrium P concentration (EPC 0) of sediments under oxi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
9
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 13 publications
(10 citation statements)
references
References 44 publications
1
9
0
Order By: Relevance
“…This supports our results with higher FSS Fe-P during low flow periods and lower Fe-P concentrations during high flow periods. Furthermore, McDowell et al (2020) reported a decrease in streambed Fe-P with sediment depth, which was also observed in our study. Phosphorus release due to Fe hydroxides/oxides dissolution with progressively more reducing sedimentary conditions at depth may explain this pattern (Parsons et al, 2017).…”
Section: 11supporting
confidence: 91%
See 1 more Smart Citation
“…This supports our results with higher FSS Fe-P during low flow periods and lower Fe-P concentrations during high flow periods. Furthermore, McDowell et al (2020) reported a decrease in streambed Fe-P with sediment depth, which was also observed in our study. Phosphorus release due to Fe hydroxides/oxides dissolution with progressively more reducing sedimentary conditions at depth may explain this pattern (Parsons et al, 2017).…”
Section: 11supporting
confidence: 91%
“…(2020) found low concentrations of H 2 O‐P in streambed sediment, with Fe‐P as the general dominating fraction at their sampling sites. These low H 2 O‐P concentrations (or corresponding fractions in other fractionation schemes) seem to be quite consistent for streambed sediment and lake sediment (Kaiserli et al., 2002; McDowell et al., 2020; Pettersson, 1998).…”
Section: Discussionmentioning
confidence: 96%
“…Several other methodological variables must be considered when measuring and interpreting EPC 0 . Redox status should be considered when planning benthic sediment sampling because it influences EPC 0 and its relation to DRP (Palmer‐Felgate et al., 2011; McDowell et al., 2020). If the goal is to characterize P exchange between the water column and the benthic sediments at the sediment–water interface (Figure 7), then sampling should avoid sediments deeper in the streambed or in stagnant zones that not only interact minimally with the water column but are also more likely to be anoxic.…”
Section: Discussionmentioning
confidence: 99%
“…Indeed, in slow lotic systems (e.g., riverine wetlands) or in parts of the stream channel with long residence times (e.g., deeper subsurface), there tends to be greater reducing conditions, which can influence EPC 0 (House & Denison, 2000; Palmer‐Felgate et al., 2011; Rahutomo et al., 2018). Consequently, this may lead to greater decoupling of DRP and EPC 0 in situ (McDowell et al., 2020). Whereas the redox interface in sediments is usually below where the majority of hyporheic exchange takes place for many streams (i.e., with dissolved oxygen approximately near saturation in the water column and moderate exchange with porewaters; Boano et al., 2014), reducing conditions in zones of longer retention times or where ecosystem respiration is high (Briggs et al., 2015) may nullify the sediment P buffer (Lewandowski & Nützmann, 2010; Smolders et al., 2017; Parsons et al., 2017).…”
Section: Discussionmentioning
confidence: 99%
“…When the sediment is in a deeper position, the water is insufficiently oxygenated and is usually in an anoxic state. Due to the reduction and dissolution of iron oxyhydroxide and the hydrolysis of calcium and phosphorus by microorganisms, phosphorus in the sediment is released into the water (Zhang et al 2018;Gao et al 2020;McDowell et al 2020). Previous studies have found that zirconium-based modified zeolite and zirconium-based modified bentonite have an effect on the unstable weakly adsorbed phosphorus (NH 4 Cl-P) and redox state phosphorus (BD-P) to the more stable metal oxide bound phosphorus (NaOH-P) and very stable residual phosphorus (Res-P) have a significant conversion effect, and significantly reduce the content of biologically available phosphorus (BAP) (Fan et al 2017;Soliman et al 2017).…”
Section: Introductionmentioning
confidence: 99%